Economic value of the water footprint of cocoa above (Theobroma Cacao) - Macías Dumes, Jairo Miguel; Pino Peralta, Sergio Leonardo (Journal of the University of Zulia, 2023)
As a strategy to promote and support the sustainable use of water resources, the water footprint of cocoa cultivation was estimated; in addition, cocoa harvesting processes were identified and characterized to evaluate their impact on water volumes used in these crops. The green water evapotranspiration and blue water depletion in the river basin were measured. The estimates were carried out following the methodology proposed by (Hoekstra et al., 2021), considering the local data necessary for estimating green and blue water use in CROPWAT 8.0. It was found that the values corresponding to the GWF are lower than the average for Ecuador and that the economic value of the water footprint of cocoa cultivation is lower than the TEV of the HH of households and businesses in a sector of Guayaquil.